Differential expression and enzymatic properties of the Na+,K(+)-ATPase alpha 3 isoenzyme in rat pineal glands. - Shyjan, A W (1990)
We have used immunoblotting and biochemical techniques to analyze expression of Na+,K(+)-ATPase alpha and beta subunits in rat pineal glands. Western blot analysis of pineal microsomal membrane fractions with antisera specific for each of the three rat alpha and two rat beta subunits revealed similar levels of expression of alpha 1 and alpha 3 subunits in pineal glands of 5-day-old rats. High levels of alpha 3 and beta 2 subunits and low levels of alpha 1 subunits were detected in adult glands. No alpha 2 or beta 1 subunits were detectable at either developmental stage. Examination of the enzymatic properties of the pineal gland alpha 3 isoform suggests that this enzyme is a ouabain-sensitive ATPase whose activity is dependent upon Na+ and K+. This ATPase exhibited a lower apparent Km for Na+ than the kidney alpha 1 isoenzyme and did not show positive cooperative Na+ activation. Our results suggest that the activity of the Na+,K(+)-ATPase alpha 3 isoenzyme may be adapted to function under conditions of hyperpolarizing transmembrane potentials.